A Case of Dextrotransposition of the Great Arteries Type I with Reversed Differential Cyanosis - Morimoto, Yuichi; Inamura, Noboru; Takemura, Tukasa (American Journal of Perinatology Reports, 2019)
Transposition of the great arteries type I is a severe congenital heart disease that induces serious cyanosis immediately after birth and death within 24 hours, unless proper treatment is administered. A few cases have presented with reversed differential cyanosis, manifesting as separated cyanosis with high SpO2 values in the lower limbs. However, there have been few reports of survivors of transposition of the great arteries type I presenting with reversed differential cyanosis. We experienced a case of transposition of the great arteries type I presenting with reversed differential cyanosis immediately after birth. The infant was urgently transported because of postnatal SpO2 of 40% in the upper limbs and 90% in the lower limbs. The echocardiographic diagnosis was transposition of the great arteries type I with a narrow foramen ovale. We immediately performed balloon atrioseptostomy, and the reversed differential cyanosis was improved. The infant seems to have presented with reversed differential cyanosis because of the foramen ovale narrowing and complicating pulmonary hypertension due to fetal circulation and characteristic of transposition of the great arteries type I. Congenital heart disease, presenting with reversed differential cyanosis, is a clinical condition requiring emergency management.
Keywords: dTGA; foramen ovale; fetal diagnosis; pulmonary hypertension; ductus arteriosus